2021
DOI: 10.4178/epih.e2021077
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment status of hepatitis C virus infection among people who have ever injected drugs in Korea: a prospective multicenter cohort study from 2007 to 2019 in comparison with non-PWID

Abstract: Introduction: Injection drug use is a major risk factor for hepatitis C virus (HCV) infection; however, limited data are available in South Korea. Thus, this study aimed to investigate the epidemiological and clinical characteristics, treatment uptake, and outcomes of HCV infection among people who inject drugs (PWID).Methods: We used the data from the Korea HCV cohort, which prospectively enrolled patients with HCV infection between 2007 and 2019. Clinical data and results of the questionnaire survey focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…9 Moreover, recent studies have shown that the treatment uptake and sustained virologic response rate of DAA did not differ between PWID and non-PWID with chronic HCV infection. 19 20 Therefore, the treatment of HCV infection in PWID should be scaled-up urgently in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, recent studies have shown that the treatment uptake and sustained virologic response rate of DAA did not differ between PWID and non-PWID with chronic HCV infection. 19 20 Therefore, the treatment of HCV infection in PWID should be scaled-up urgently in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, WHO proposed the goal of eliminating viral hepatitis as a public health threat by 2030 8 -a 90% reduction in new infections and a 65% reduction in mortality. Whereas most studies on viral hepatitis infection primarily focused on HBV 9 or specially HCV exposed populations such as people who inject drugs (PWID) and men who have sex with men (MSM) [10][11][12] , studies among pregnant women were scarce. To achieve the goal of eliminating HCV as a public health threat, reducing the disease burden of society and decreasing new HCV infections, study on HCV pregnant women and HCV mother-to-children transmission is essential.…”
mentioning
confidence: 99%